Abnormal Proteolytic Processing of von Willebrand Factor Arg611 Cys and Arg 611 His - Nishikubo, Toshiya; Christophe, Olivier; Lavergne, Jean-Maurice; Obert, Bernadette; Nonami, Kyoko; Takahashi, Yukihiro; Yoshioka, Akira; Meyer, Dominique; Girma, Jean-Pierre (Thrombosis and Haemostasis, 1997)
The structural and functional properties of plasma and platelet vWF were studied in 8 patients (5 unrelated families) with vWD demonstrating a mutation at position 611 (R611C or R611H). Following reduction, electrophoresis and immunoblotting with a polyclonal anti-reduced vWF antibody, abnormal proteolysis of vWF was demonstrated in plasma and to a lesser extent in platelets from all patients, leading to the formation of a unique 209 kDa fragment undetectable in control as well as in type 2A, 2B or 2N vWF. Immunoblotting with MoAbs to reduced vWF showed that the C-terminal end of the 209 kDa fragment was located beyond residue 1744 of the subunit and that its N-terminus was between residues 523 and 1114. Multimeric analysis of patients vWF showed an abnormal pattern in both plasma and platelets, with a moderate decrease of the HMW multimers together with a significant increase of the lowest MW forms. The specific sensitivity of vWF R611C and vWF R611H to proteolysis was further evidenced using V-8 protease. In all patient’s samples the enzyme produced a unique monomeric 80 kDa fragment, absent in V-8 digested normal vWF, which overlapped the N-terminal part of the subunit. The functional analysis of vWF showed a markedly decreased affinity of mutated plasma vWF for platelet GPIb in the presence of ristocetin. Infusion of DDAVP in two of these patients did not lead to significant platelet count change. It induced a limited increase of the HMW multimers in plasma together with a poor correction of the vWF binding to platelet GPIb. In conclusion, our data demonstrate that in addition to a normal proteolysis, vWF mutated at position 611 undergoes a specific cleavage in plasma and platelets. In contrast to the increased proteolysis observed in type 2A and 2B patients’ plasma, this additional cleavage produced a unique 209 kDa species but maintained a HMW multimer-like structure of vWF R611C and R611H.